Addressing Fear of Cancer Recurrence: A Cognitive-Existential Psychosocial Intervention for Cancer Survivors - Tomei, Christina (Université d'Ottawa / University of Ottawa, 2017)
Fear of cancer recurrence (FCR) is defined as “fear, worry, or concern relating to the possibility that cancer will come back or progress (Lebel et al., 2016, p. 3266). FCR is the most frequently reported concern identified among cancer survivors (Baker, Denniston, Smith, & West, 2005; Lebel, Rosberger, Edgar, & Devins, 2007). Although approximately 50% of cancer survivors experience moderate-to-high levels of FCR (Simard et al., 2013), few psychosocial interventions exist that directly target this construct. The overarching study objectives were: (a) to adapt a manualized, 6-week, cognitive-existential group therapy intervention for FCR to an individual format; (b) to pilot-test the feasibility, acceptability, and satisfaction of this individual intervention on n=3 participants; and (c) to further pilot-test the efficacy of the individual intervention on n=25 participants, via a randomized controlled trial (RCT). In study 1, n=3 cancer survivors (1 male, 2 females) completed the one-on-one therapy intervention for the psychological treatment of FCR. Sessions were 60-90 minutes long, and included cognitive restructuring exercises, behavioural experiments, relaxation techniques, existential processing of the here-and-now, and finding meaning in life post-diagnosis. Participants completed questionnaire packages throughout the intervention and an exit interview to determine their overall feedback on the intervention. Quantitative analyses revealed downwards trends in fear of cancer recurrence and cancer-specific distress across participants. Qualitative analyses of the exit interviews revealed that all participants found the intervention useful, and that the sessions had favourable pacing and length. In study 2, the FCR intervention was further pilot-tested via an RCT. Twenty-five female cancer survivors were randomized to an experimental group or a wait-list control group. Sessions included cognitive restructuring techniques, behavioural experiments, confronting existential distress, and relaxation exercises. Nineteen women (n=9 intervention, n=10 control) completed the 6-week therapy intervention, and completed questionnaire packages at pre-, post- and 3-month follow-up. Between-within ANOVAs revealed significant interactions in the primary outcome measure of FCR, and secondary outcome measures of cancer-specific distress and uncertainty in illness for participants in the experimental group. Repeated measures ANOVAs revealed reductions in FCR, cancer-specific distress, uncertainty in illness, reassurance-seeking, cognitive avoidance, and intolerance of uncertainty, and revealed improvements in positive reinterpretation and growth, use of emotional support and mental health (improved quality of life) for participants in the experimental group, as compared to the wait-list control group. The variables that changed either maintained or improved at follow-up. Results from this study demonstrate promising results in addressing FCR in cancer survivors via a cognitive-existential intervention. Future research should continue investigating the specific therapeutic ingredients that are most effective for the psychological treatment of FCR.
Keywords: Fear of Cancer Recurrence; Psychosocial Intervention; Psychosocial Oncology; Pilot Study; Randomized Controlled Clinical Trial; Coping